Práticas de letramentos literário e digital com contos de fadas - Santos, Mônica Andrade (2024)
The formation of literary readers through the lens of digital literacy involves mediation of literary reading through the use of Digital Information and Communication Technologies (DICTs). Literary literacy becomes more dynamic when we use technological tools to expand the meanings of literary texts. In the process of school reading, the relevance of digital devices is understood as a possibility of accessing literary texts and a way of disseminating students' productions. In this sense, this intervention proposal aims to investigate how literary and digital literacies contribute to the formation of literary readers and the development of hybrid text production skills, typical of multiliteracies. The theoretical basis is divided into thematic axes: digital literacies: Maria Teresa Freitas (2010, 2015) and Roxane Rojo (2012, 2019); stages of literary literacy: Rildo Cosson (2020, 2023); aspects of subjective reading: Annie Rouxel; and perspectives of multimodal reception: Carlos Magno Gomes (2019). Based on the action- research methodology, fairy tale reading workshops were developed for seventh-grade elementary school classes, which provided an expansion of the literary repertoire of readers. In addition, the workshops encouraged reflections on various themes addressed in fairy tales, allowing students to correlate such narratives with contemporary social issues. Multimodal reading practices brought positive results, as they involved participants in collaborative actions, both in the literary reading phase and in the production of multimodal texts, with the help of digital language. Based on the experiences of mediating literary reading, a Multimodal Fairy Tale Reading Book was created as the final product. This material aims to significantly support the pedagogical action of Portuguese language teachers, offering resources and strategies that can be adapted to various educational practices, and is also considered a practical guide for the implementation of similar workshops in other school contexts.